Questions & Answers

Question

Answers

Answer

Verified

91.8k+ views

The answer to this question lies in the product of the two expressions. Let us multiply the two given expressions.

$ \Rightarrow \left( {x + 5} \right)\left( {2{x^2} + 7x - 10} \right)$

We will distribute the first expression such that each term of the first expression can be multiplied with every term of second expression.

$ \Rightarrow x\left( {2{x^2} + 7x - 10} \right) + 5\left( {2{x^2} + 7x - 10} \right)$

Now, we will multiply the bracket term, and we get

$ \Rightarrow 2{x^3} + 7{x^2} - 10x + 10{x^2} + 35x - 50$

Next step is to group the like terms. (Like terms are those terms which have same variables and their powers, for example, $45{x^4}$ and $\dfrac{{23}}{7}{x^4}$ are like terms)

$ \Rightarrow 2{x^3} + \left( {35x - 10x} \right) + \left( {10{x^2} + 7{x^2}} \right) - 50$

Now, we will add or subtract the like terms.

$ \Rightarrow 2{x^3} + 25x + 17{x^2} - 50$

This is the product of the given two expressions. We have been asked to find the product in standard form. In our case, we need to find the standard form of writing a cubic equation in one variable. It is defined as follows:

$ \Rightarrow a{x^3} + b{x^2} + cx + d = 0$

Let us write our equation in the standard form.

$ \Rightarrow 2{x^3} + 25x + 17{x^2} - 50$

On rewriting we get

$ \Rightarrow 2{x^3} + 17{x^2} + 25x - 50$